The Leasing Contract. Harmonizing National Legislation with the Lease Specific International Norms - Gheorghe Dinu; Raluca Antoanetta Tomescu (EIRP Proceedings, 2016)
By elaborating the proposed work, we want to bring theoretical contributions and enter a scientific domain which may not be at the beginning of its course to Romanian society, but which we consider to be able to handle improvements under doctrinaire and practical aspects. Objectively, we intend to reinforce the “statute” of leasing operations on a national level, operations which are still searching for their own identity, lacking any “legacy” gained from experience or historical post-December accumulations, and what has been gained has been assumed in a rush, under the influence of the Romanian society’s processes of democratization and European integration and are mechanical accumulations/teachings which resulted from the enforcement and necessity of complying with certain treaties and agreements which have not been sufficiently analyzed. Because they were taken in fractions, a series of norms resulted, lacking the consistency and sufficiency needed to improve education in the leasing domain, which has often led to contractual imbalances and a considerable decrease of the leasing market in Romania.